A graduação nos trabalhos da ANPEd: (1996-2003) - Mindal, Clara Brener (2006)
This bibliographic-documental investigation aims at building a map of the aspects regarding graduate (four-year college) studies that stood out in the academic production presented in the ANPEd (National Association for Post-graduate studies and Research in Education) meetings between the years 1996 and 2003. In order to do so, we have analysed 163 papers contained in the ANPEd historical CD-ROM which gathers documents up to 2001 and from the 2002 and 2003 annual meeting CD-ROMs, selecting those that deal with higher education and approach aspects of graduate studies. Special attention was given to aspects that refer to the relationship between teaching and research in this level of teaching. We set off from a bibliographic review that situates graduate studies into higher education and universities and analyses teaching and research functions as inserted in the history of higher education in Brazil and in the expectations for the XXI century. For the data analyses we based on studies of Brazilian authors that produced syntheses of the academic production in theses, dissertations and national periodicals on higher education and teachers training. The texts that have been analyzed originate mainly from public universities; 30% refer to the relationship between teaching and research as inserted in analises of the history, financing, structure or organization of the Brazilian higher education; 38% of the texts approach in classroom investigations or documental and bibliographic research the courses, disciplines, curricular structure, pedagogical practices, teaching/learning processes or several concepts from teachers and students, among others. Although the production that focuses on graduate studies increases in this period, it tends to decrease in the last years, as opposed to the texts that approach the teachers training for higher education, which show an increase. We find a greater incidence of studies on teachers training courses and less on another graduate courses, as well as a recurrence of studies about courses as Pedagogy and Mathematics. The field of research about graduate students is little explored and investigations on quality and working conditions for professors, as well as substitute professors are practically ignored in the academic production